Modelling and analysis of the flood risk at Cavaillon City, Haiti. Issue 2 (1st April 2018) - Joseph, Adermus; Gonomy, Nyankona; Zech, Yves; Soares-Frazão, Sandra
Abstract : In Haiti, the vulnerability of urban populations in river flood corridors has disastrous socio-economic consequences on the living conditions of these communities. Mapping of areas prone to this type of risk is not sufficiently developed in Haiti, which complicates the implementation of strategies for the effective management of flood risk. This paper presents a methodological approach allowing to draw up a risk map of the city of Cavaillon, which is confronted to periodic flooding by the Cavaillon river flowing through the city. The reconstruction of the riverbed and floodplain geometry using a differential GPS and a novel drone-based photogrammetry technique made it possible to construct a hydraulic model of the river and to calculate the flow in the river for scenarios corresponding to different periods of return. The vulnerability of the different areas in the city was established using an Analytic Hierarchy Process. Various criteria of vulnerability were identified and their respective weight progressively determined from discussions between local decision-makers. Finally, considering the extent of the inundated area following recent Hurricane Matthew that particularly affected the zone, a vulnerability mapping was drawn for the town of Cavaillon.